The consult manual of internal medicine - Rosen, Harry (MedConsult Pub., 2006)
A valuable pocket companion to be used often for rapid and useful information, with the right amount of explanation, enabling a higher degreeof learning during medical school, residency, and beyond; being both easily accessible on the wards, and enjoyable to read in preparation for examinations, presentations, and patient rounds